Ni(Pt) alloy silicidation on (100) Si and poly-silicon lines - Pey, Kin Leong (2013)
The roles of the Pt in Ni-(5 at.% Pt) alloy reaction on narrow c-Si (100) and polysilicon (poly-Si) lines by rapid thermal annealed (RTP) in the range of 400 to 900 °C were studied. By the addition of Pt as an alloying element, the phase stability of NiSi on Si(100) was enhanced and the retardation of NiSi2 was achieved by forming Ni(Pt)Si up to 900 °C. In addition, the agglomeration behavior has slightly improved. On narrow poly-Si lines, the addition of Pt improves slightly the layer inversion, which involves the bilayer reversal of silicide and poly-Si. Despite this, the Ni(Pt)Si phase on the narrow poly-Si lines is remarkably stable up to 800–900 °C. The implementation of the developed Ni(Pt) alloy silicide scheme to the state-of-the-art transistors shows that the electrical performance of the Ni(Pt)-silicided MOSFETs has been improved due to the enhanced stability of the Ni(Pt)Si as compared to the pure NiSi at relative high silicidation temperatures.